Integrative tasks and learning in junior high school - Miranda, Naiviv; Pirez, Yudisleidys; García, Jorge (Transformación, 2012)
The quality of learning is one of the challenges of national education in Cuba. This paper is intended to examine the rationale of planning, implementing and evaluating integrative tasks, as a means to enhance the quality junior high school services. Several methods and procedures were used: The systemic and structural approach, analysis-synthesis, observation, interviews and surveys among them. Pupil’s learning shortcomings and potentials were identified before devising a set of procedures and hints for an extensive use of integrative tasks.